Sports accidents in open and closed spaces. A systematic review - Mateo-López, Miguel Ángel; Salvador-Pérez, Federico; Zurita Ortega, Félix; Melguizo Ibáñez, Eduardo; Ubago Jiménez, Jose Luis; González Valero, Gabriel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The increase in the demand for and practice of physical activity is increasing the number of sports injuries and accidents. In view of this premise, the aim of this research is to analyse the accident rate in the practice of physical activity in different modalities in open and closed spaces. To this end, the PRISMA statement has been followed, covering the articles located in the Web of Science over the last five years. The research terms were "sport", "physical activity" and "accident" and included research with a quantitative and qualitative methodological design, obtaining a body of 20 articles. The main results obtained in outdoor sports show that the activities that cause the most sports accidents are those that take place in the natural environment, and that the most experienced practitioners are those who suffer the most serious accidents in winter sports. Finally, in indoor sports, the most alternative modalities were analysed, however, it was not possible to establish the causes and factors that occurred, due to the modality of the sports.